Resurrection walk eaudiobook - Connelly, Michael (Lincoln Lawyer, 2023)
From #1 New York Times bestselling author Michael Connelly: Lincoln Lawyer Mickey Haller enlists the help of his half-brother, Harry Bosch, to prove the innocence of a woman convicted of killing her husband. Defense attorney Mickey Haller is back, taking the long shot cases, where the chances of winning are one in a million. After getting a wrongfully convicted man out of prison, he is inundated with pleas from incarcerated people claiming innocence. He enlists his half brother, retired LAPD Detective Harry Bosch, to weed through the letters, knowing most claims will be false. Bosch pulls a needle from the haystack: a woman in prison for killing her husband, a sheriff's deputy, but who still maintains her innocence. Bosch reviews the case and sees elements that don't add up, and a sheriff's department intent on bringing quick justice in the killing of one of its own. Now Haller has an uphill battle in court, a David fighting Goliaths to vindicate his client. The path for both lawyer and investigator is fraught with danger from those who don't want the case reopened and will stop at nothing to keep the Haller-Bosch dream team from finding the truth. Packed with intrigue and courtroom drama, Resurrection Walk shows once again that Michael Connelly is "the most consistently superior living crime fiction author" ( South Florida Sun Sentinel).